2021
DOI: 10.1021/acsenergylett.1c00496
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Potential Control for Accurate Studies of Electrochemical CO Reduction

Abstract: CO reduction studies over nanostructured copper catalysts are hindered by copper's instability in alkaline conditions, which results in dissolution during immersion into the electrolyte, leading to ill-defined catalyst morphologies and loadings. Immersing catalysts under potential control can alleviate this problem, but an experimental approach for cells generally used for CO reduction experiments is lacking. We demonstrate that by using an auxiliary electrochemical cell, electrodes can be introduced under pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…In fact, the application of a cathodic potential during the cell assembly was proven essential to preserve the activity of Cu nanocatalysts smaller than 10 nm. 18 Various evidence suggests that the Cu catalyst reconstruction continues under reducing potential during CO2RR. A study based on in-situ X-ray absorption and diffraction showed changes in surface coordination of Cu atoms in response to the applied potential.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the application of a cathodic potential during the cell assembly was proven essential to preserve the activity of Cu nanocatalysts smaller than 10 nm. 18 Various evidence suggests that the Cu catalyst reconstruction continues under reducing potential during CO2RR. A study based on in-situ X-ray absorption and diffraction showed changes in surface coordination of Cu atoms in response to the applied potential.…”
Section: Introductionmentioning
confidence: 99%
“…Another, and much easier, approach is to mitigate OCP by applying potential control and never let the catalyst go to OCP. 47 We also note the Pourbaix diagram construction is grounded on thermodynamics. Kinetics could also contribute to the stabilization and/or dissolution of an electrocatalyst in aqueous solution.…”
mentioning
confidence: 99%
“…One approach is to develop new active nonprecious HER catalysts with a large stability window and minimal OCP. Another, and much easier, approach is to mitigate OCP by applying potential control and never let the catalyst go to OCP …”
mentioning
confidence: 99%
“…Since the liquid volume of the electrochemical cell can be different among experiments, where the cell is repeatedly mounted and dismounted from the mass spectrometer, the approach based on knowledge of the micro‐capillary, which remains the same as long as the same chip is used, is chosen for this study. Moreover, the well‐defined nature of micro‐fabricated capillaries as mass spectrometry inlet systems has been extensively verified in previous studies [13,16,17] . In order to calibrate the mass spectrometer signal, nitrogen gas with 315 ppm of ammonia was used as auxiliary gas and the system was left to equilibrate for at least 10 hours until the ammonia signal reached a steady state (Figure S4 This was performed prior to the non‐aqueous electrochemical measurement shown earlier in Figure 3.…”
Section: Resultsmentioning
confidence: 88%
“…been extensively verified in previous studies. [13,16,17] In order to calibrate the mass spectrometer signal, nitrogen gas with 315 ppm of ammonia was used as auxiliary gas and the system was left to equilibrate for at least 10 hours until the ammonia signal reached a steady state (Figure S4 This was performed prior to the non-aqueous electrochemical measurement shown earlier in Figure 3. With knowledge of the capillary flow, which can be calculated according to Henriksen et al, [18] the ammonia molar flow into the mass spectrometer can be derived and a calibration factor determined (details see SI).…”
mentioning
confidence: 99%